Blended Learning-Based Self-directed Learning on Classroom Action Research Training to Improve Teacher Competency Research - Soeharto, Gunawan Setiadi, Soetarno Joyoatmojo, Sajidan & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Although classroom action research (CAR) is considered useful for teacherdevelopment but this activity has not been implanted yet effectively in Indonesia. Inthis paper, we report the alternative way to overcome this problem. It addresses howblended learning support self-directed learning and enhance teacher competencyresearch. Through questionnaire, interview and document analysis, the result showedthat blended learning-based self-learning can improve teachers performance inconducting classroom action research (CAR) and enhance their ability in compilingthe research report.Keywords: self-directed-learning, blended learning,classroom action research, teachercompetency research.